2021
DOI: 10.1140/epjp/s13360-021-02284-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic behaviour of velocity of applied magnetic field on unsteady MHD Couette flow of dusty fluid in an annulus

Abstract: This research work inspects mass transport phenomenon of Saffman’s dusty fluid model for transient magnetohydrodynamics fluid flow of a binary mixture passing through an annular duct. Particularly, effort has been devoted to theoretically explore the role of velocity of applied magnetic field. Here, our treatment of the governing momentum equations accountable for the flow is done using the classical Laplace transform technique and Riemann-Sum Approximation. The effects of the physical parameters such as time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Using dimensionless parameters defined in (5), the equations governing the problem become dimensionless in the form of relations (7)(8).…”
Section: Gr η= Rementioning
confidence: 99%
See 1 more Smart Citation
“…Using dimensionless parameters defined in (5), the equations governing the problem become dimensionless in the form of relations (7)(8).…”
Section: Gr η= Rementioning
confidence: 99%
“…Laplace transform technique has been utilized and results indicated the act of suction on perforated walls and the increase of oscillation frequency reduce the effectiveness of skin frictions on both walls of cylinder. Additionally, there is further research [6][7][8][9] conducted to investigate fluid flow and heat transfer in an annulus. Amouzadeh et al [10] surveyed analytically the influence of suction/injection on MHD fluid flow in a vertical annulus by considering radial heat generation or absorption with the aim of cooling electronic equipment.…”
Section: -Introductionmentioning
confidence: 99%
“…In the existence of a chemical reaction, Afikuzzaman et al (2018) reported heat transfer and free convective flow across an upright plate with MHD. Dusty fluid in an annulus with hydrodynamic velocity behavior was studied by Jha and Gambo (2022). A magnetic field was found to impact Couette flow.…”
Section: Introductionmentioning
confidence: 99%